Lidia's Italy in America - Bastianich, Lidia (Knopf, 2011)
"In this companion book to her upcoming public television series, Lidia takes us on a road trip into the heart of Italian American cooking today. As she explores the multifaceted approach to this utterly delectable and distinctive cuisine, we come to see that every kitchen and every Italian community is different. Clues are buried in each dish: the Sicilian-style semolina bread and briny olives in New Orleans muffaletta sandwiches, the Neapolitan crust of New York pizza, and the smoky provola that tops braised chicken breasts in Philadelphia. She talks with creative cooks all over the country--farmers, housewives, butchers, fishermen, and food entrepreneurs--about the ingredients they use, their kitchen secrets, and of course, their favorite recipes: from Rhode Island Clams Casino and Baltimore Crab Cakes to Bronx Eggplant Parmesan and Boston Cream Cakes. And she gives recognition where it is long overdue to the many industrious Italians across the country who have honored the traditions of their homeland in a delicious new style. A loving exploration of a fascinating cuisine--as only Lidia could give us"--Provided by publisher.